Facial Rejuvenation: Effectiveness of the Facelift Combined with Stem Cells and Lipograft Techniques - Torres, Dennis Steve Vargas; Mello, Arnaldo Almendros (Journal of Posthumanism, 2025)
A documentary review was carried out on the production and publication of research papers related to the study of the Facial Rejuvenation and Lifting variables. The purpose of the bibliometric analysis proposed in this document was to know the main characteristics of the volume of publications registered in the Scopus database during the period 2018-2023, achieving the identification of 163 publications. The information provided by this platform was organized through graphs and figures categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics have been described, the position of different authors regarding the proposed theme is referenced through a qualitative analysis. Among the main findings made through this research, it is found that the United States, with 48 publications, was the country with the highest scientific production registered in the name of authors affiliated with institutions in that nation. The Area of Knowledge that made the greatest contribution to the construction of bibliographic material regarding the study of the Facial Rejuvenation and Lifting variables was Medicine with 155 published documents, and the most used Type of Publication during the period indicated above were Journal Articles with 66% of the total scientific production.